1998
DOI: 10.1093/emboj/17.19.5588
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of IL-6 and soluble IL-6R causes nodular regenerative hyperplasia and adenomas of the liver

Abstract: Studies with tumor necrosis factor p55 receptor-and interleukin-6 (IL-6)-deficient mice have shown that IL-6 is required for hepatocyte proliferation and reconstitution of the liver mass after partial hepatectomy. The biological activities of IL-6 are potentiated when this cytokine binds soluble forms of its specific receptor subunit (sIL-6R) and the resulting complex interacts with the transmembrane signaling chain gp130. We show here that double transgenic mice expressing high levels of both human IL-6 and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 33 publications
(58 reference statements)
4
84
1
1
Order By: Relevance
“…In addition, when IL-6-transfected BCC cells were transplanted into nude mice, they also enhanced tumor size and incidence. Our current ®ndings are in agreement with other studies which showed that under the control of liver-speci®c promoters, coexpression of IL-6 and IL-6Ra in mice resulted in hepatic hyperplasia and adenomas (Maione et al, 1998). Transplantation of the viral IL-6-expressing NIH3T3 cells into athymic mice caused tumor formation at injection site as well as other pathologic disorders, including hematopoiesis in the blood cells, hepatosplenomegaly and polyclonal hypergamma globulinemia (Aoki et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, when IL-6-transfected BCC cells were transplanted into nude mice, they also enhanced tumor size and incidence. Our current ®ndings are in agreement with other studies which showed that under the control of liver-speci®c promoters, coexpression of IL-6 and IL-6Ra in mice resulted in hepatic hyperplasia and adenomas (Maione et al, 1998). Transplantation of the viral IL-6-expressing NIH3T3 cells into athymic mice caused tumor formation at injection site as well as other pathologic disorders, including hematopoiesis in the blood cells, hepatosplenomegaly and polyclonal hypergamma globulinemia (Aoki et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…In IL-6 single transgenic mice, no significant hepatic phenotype is observed, but IL-6/sIL-6R double transgenic mice show hepatocellular hyperplasia and adenomas. 3 In this study, exogenous rhIL-6 treatment reversed the decline of increased liver mass by increasing the hepatocyte BrdU labeling index. Several of the IL-6 Ϫ/Ϫ mice that received long-term rhIL-6 treatment also developed marked extramedullary hematopoiesis in the liver and the spleen and a very high hepatocyte BrdU labeling index, which is similar to the reaction of the experimental animals treated, IL-6/sIL-6R double transgenic mice.…”
Section: Discussionmentioning
confidence: 54%
“…For example, liver regeneration after partial hepatectomy (PH) is delayed in IL-6 Ϫ/Ϫ mice, 1,2 whereas IL-6/sIL-6R double transgenic mice develop hepatocellular hyperplasia and adenomas. 3 Although data on the in vitro effects of IL-6 on hepatocyte proliferation are conflicting, 4,5 there are at least two mechanisms by which IL-6/gp-130 promotes BEC growth in vitro. IL-6 is able to directly stimulate BEC DNA synthesis 6 and inhibit apoptosis, via an increase of the bcl-2/ bax ratio.…”
mentioning
confidence: 99%
“…Its expression is elevated in human hepatocellular carcinoma (13). Overexpression of interleukin-6 (IL-6) and soluble IL-6 receptor in transgenic mice leads to massive elevation of Igfbp1 and the development of hepatocellular hyperplasia and adenoma (14). Igfbp1 is critical for proper control of the hepatocyte cell cycle, and regulates mitogenic signaling by activating MAPK/ERK (mitogen-activated protein kinase/extracellular signal-regulated kinase) and C/EBP (CCAAT/enhancer binding protein) ß protein level in vivo (15).…”
Section: Discussionmentioning
confidence: 99%